Lazer, circo e arte: possíveis experiências em um contexto de práticas em transformação a Spasso Escola Popular de Circo como cenário e percurso - Paula Miranda Alves Pimenta (2014)
The present study focuses on circus practices experiences as a possibility of transformation. Aiming to understand what are the contributions of the artistic experience - lived in the Spasso Popular Circus School as a leisure spaces and time - to the process of cultural and human formation, an ethnographic study was conducted in which to describe the changes observed during lessons circus workshop and reported by interviewees, it was possible to recognize what is learned in the circus practice. These transformations are made possible as the activities are by their experience, as proposed Larossa (2008) as something that touches and transforms us. The art lived as experience refers to the propositions of John Dewey recognizes that the aesthetic experience as a retrieving the origins of aesthetic and beautiful in the natural needs of man, understanding it as part of its essence. Thus, the artistic experience is presented as a possibility of relational learning that take place in contact with the circus arts and the relationship of the subject with people, with objects and space. The fieldwork revealed that, in addition to other sensitive learning techniques learned were discussed at the meeting with the circus universe, transforming the lives of these individuals. The circus as a social practice, is the result of a process of change and permanence which today can be experienced in different ways, configuring it as a possibility of aesthetic learning. The art which had its origins in the rituals historically turned into spectacle, becoming something away from people's lives. To recover a notion of art as something that can be lived daily was possible to recognize the transformative potential of artistic experiences. By the same token we can recognize the potential of leisure as a possibility for the transformation of people and be experienced as part of the organization of their lives.